2007
DOI: 10.1128/aem.02378-06
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure and Dynamics of Dark Fire-Cured Tobacco Fermentation

Abstract: The Italian Toscano cigar production includes a fermentation step that starts when dark fire-cured tobacco leaves are moistened and mixed with ca. 20% prefermented tobacco to form a 500-kg bulk. The dynamics of the process, lasting ca. 18 days, has never been investigated in detail, and limited information is available on microbiota involved. Here we show that Toscano fermentation is invariably associated with the following: (i) an increase in temperature, pH, and total microbial population; (ii) a decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 55 publications
4
83
0
Order By: Relevance
“…These studies identified several specific bacterial species present in tobacco products including Actinomycetes spp. (Di Giacomo et al 2007), Bacteriovox sp. (Zhao et al 2007), Kurthia spp., Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified several specific bacterial species present in tobacco products including Actinomycetes spp. (Di Giacomo et al 2007), Bacteriovox sp. (Zhao et al 2007), Kurthia spp., Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…These comprise species from the families Pseudomonadaceae, Staphylococcaceae , Lactobacillaceae , Enterobacteriaceae , Enterococcaceae , Aerococcaceae , Corynebacteriaceae , among others, and include potential human and respiratory pathogens (Di Giacomo et al, 2007; Huang et al, 2010; Sapkota et al, 2010; Su et al, 2011). Furthermore, tobacco and tobacco smoke have been shown to harbor microbial derived toxins and secondary metabolites (Hasday et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It's high activity inhibits the activity of certain microorganisms that are essential for fermentation (Di Giacomo et al, 2007). During fermentation the content of catalase is reduced, and in the context of these data and the results of this study, where the highest activity of catalase show leaves harvested in 2012 for all tested varieties.…”
Section: Resultsmentioning
confidence: 69%